Improving Railway Infrastructure Pricing System - Nikolova, Hristina (Research Papers, 2007)
The proposed paper presents an analysis of the railway infrastructure supply and demand as well as its management. It discusses over the applicable approaches for the estimation and measurement of marginal social costs and it studies the opportunities of improvement of the planning and control of these costs in Bulgarian State Railways. Reviewed approaches are brought out on the base of a number of studies and projects on measurement of the marginal social costs of transport held in EU member states. In this study the railways infrastructure charging tariff is analyzed and its advantages and disadvantages are, therefore, specified. In addition, the main problems occurring as a result of application of the tariff are explained and the opportunities for their solving are suggested. As a conclusion, the author derives the main directions of influence of the infrastructure charges over the efficiency of the railway transport and over the infrastructure use. Finally, the opportunities of improvement of the railway infrastructure charging scheme are suggested along with direct results which they could yield.